A CASE STUDY: IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH PICTURESIN SMK SWASTA TAMAN PENDIDIKAN - Mungkap Mangapul Siahaan (Program Studi Pendidikan Bahasa Inggris FKIP, 2020)
This research agrees with the finding data which is improving students’ speaking ability through series picturesin speaking lesson in SMK Swasta Taman Pendidikan on Jalan Radjamin Purba, SH Pasar I-A Perdagangan, Kecamatan Bandar – Kabupaten Simalungun. An action research class is conducted to define the solution of the improving students’ achievement in speaking. Through this research, the researcher shared the result of the students speaking capabilities after using series pictures. The datum shows the comparison between students’ speaking ability using pictures and without using pictures. The design of this research was the experimental quantitative research which is aim to know the effect of the series pictures in the students speaking learning activity. In collecting the data of the research, the researcher had to do three steps as pre-test, treatment and post-test. The result of the tests shows that students’ speaking ability is improved through using pictures series